2015
DOI: 10.1177/1060028015595642
|View full text |Cite
|
Sign up to set email alerts
|

Noninferiority of Inhaled Epoprostenol to Inhaled Nitric Oxide for the Treatment of ARDS

Abstract: Inhaled epoprostenol was noninferior to inhaled nitric oxide with regard to ventilator-free days from day 1 to day 28 in ARDS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 59 publications
(41 reference statements)
3
50
0
Order By: Relevance
“…In our clinical practice, we often use iEPO for severe hypoxemic patients without pulmonary hypertension or right ventricular dysfunction during mechanical ventilation [5][6][7]. We do not have experience with iEPO delivery via HFNC in this population before mechanical ventilation.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our clinical practice, we often use iEPO for severe hypoxemic patients without pulmonary hypertension or right ventricular dysfunction during mechanical ventilation [5][6][7]. We do not have experience with iEPO delivery via HFNC in this population before mechanical ventilation.…”
Section: Limitationsmentioning
confidence: 99%
“…Inhaled epoprostenol (iEPO) is a pulmonary vasodilator which has been used off-label to treat pulmonary hypertension in the United States for over 15 years [1]. Inhaled epoprostenol has shown similar effectiveness in reducing pulmonary arterial pressure and improving oxygenation as inhaled nitric oxide (iNO) among mechanically ventilated patients [2][3][4][5][6][7]. Compared to iNO, iEPO is cost-saving and has become a common treatment in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…In the 94 patients with ARDS managed similarly otherwise, the group treated with inhaled epoprostenol had no fewer ventilator-free days and no worse safety outcomes than those treated with nitric oxide. 6 Following description of the technology that enabled administration of inhaled prostaglandins, there has been modest interest in their application in ARDS. In a large-scale series, inhaled vasodilators (which include both prostaglandins and nitric oxide) were used in only 7.7% of patients with ARDS.…”
mentioning
confidence: 99%
“…42,46 In addition to finding similar relative efficacy in therapy, these studies found that the use of iEPO was associated with a significant cost savings of 10-20-fold. A study 47 showed the noninferiority of iEPO versus iNO in terms of ventilator-free days, in addition to other similar clinical outcomes between the two regimens in patients with ARDS. The concept of using iEPO rather than iNO is rigorously supported by prospective active-comparator trials as well.…”
Section: Inhaled Vasodilatorsmentioning
confidence: 99%
“…Limiting the ability of care providers to "override" non-critical care medications from automated dispensing cabinets may also be an area of operational control to pursue for medications with rising prices. One extreme measure proposed for low-volume very high-cost medications is to call care providers prior to every dispensed dose to ensure that medication 30,32 Prescribing protocol for an institution developed by a multidisciplinary group across all ICU settings Pharmacist-directed stewardship to enforce prescribing guidelines Use of oral a 2 -agonists to replace continuous-infusion dexmedetomidine Recombinant factor VIIa 37,40 Fixed-dosing protocol for warfarin-induced intracranial hemorrhage Implementation of pharmacist-driven critical bleeding management protocol Inhaled vasodilators 42,[45][46][47][48][49] Protocols regarding setup and weaning Substitution of inhaled prostacyclin Medications with relatively newer price increases Albuterol/ipratropium metered-dose inhaler 53,54 Switch to nebulizer products Minimize all inhaled bronchodilator use Chlorothiazide [56][57][58] Pharmacist stewardship program to enforce prescribing guidelines Substitution of oral adjunctive therapy for diuresis (e.g., metolazone) Nitroprusside [59][60][61] Substitution of nicardipine or clevidipine (branded products but are nonetheless cost saving) Vasopressors 62 Use of midodrine to reduce duration of vasopressor use ICU = intensive care unit.…”
Section: Review Operational Procedures For Drug Acquisition and Prepamentioning
confidence: 99%